Pengaruh Kompetensi Pedagogik dan Profesional terhadap Kinerja Guru SMP Negeri di Kecamatan Pangkalan Lampam - Vivin Ekawati; Happy Fitria; Mulyadi Mulyadi (Departement of Mathematics Education, 2023)
This research is based on a need for a better understanding of the characteristics and conditions of students when evaluating assessments. as well as the existence of a large proportion of teachers who have not been able to apply information technology in an effort to increase the effectiveness of student learning. The purpose of this research is to describe and analyze the influence of pedagogic competence and professional competence together on the performance of teachers in state middle schools in Pangkalan Lampam District. This research was conducted in all public middle schools in Pangkalan Lampam District, namely Public Middle School 1 Pangkalan Lampam, Middle School 2 Pangkalan Lampam, Middle School 3 Pangkalan Lampam, Middle School 4 Pangkalan Lampam and Middle School 5 Pangkalan Lampam, Ogan Komering Ilir Regency, and took place from June to October 2022. This study used a type of correlational quantitative research method after the fact. Sampling techniques that can be used include technical probability sampling as well as non-probability sampling. The total number of state Junior high school teachers in Pangkalan Lampam District is 102. F valuecount of 19.286 and the value of FTable of 3.11 then Fcount > FTable which means Ho is rejected and Ha is accepted, meaning that the pedagogic competency and professional competency variables have a significant effect on teacher performance variables. The R Square value is 0.331, thus the coefficient of determination is 33.1%, so it can be concluded that the influence of pedagogical competence and professional competence on teacher performance is 33.1%, and the remaining 67% is influenced by other factors not included in this variable.